Structural Barriers to Climate Finance Access: The Conditionality Paradox in Indonesia’s NDC Commitments - Shinta Kumala Sari (Research Horizon, 2026)
This study is motivated by the growing gap between Indonesia’s increasing conditional climate commitments under the Paris Agreement and its limited access to financing from the Green Climate Fund (GCF). It aims to analyse how the structural design of the global climate finance architecture constrains Indonesia’s access to GCF funding. The study employs a qualitative document analysis of Indonesia’s NDC submissions, GCF project data, and national and international policy reports. The findings reveal a conditionality paradox, where Indonesia’s conditional financing needs have increased significantly from USD 247 billion in 2016 to USD 472.6 billion in 2025, while GCF access remains below 0.2% of these needs. These constraints are not solely due to domestic capacity limitations but are also embedded in the complex institutional requirements of the GCF, which have not fully adapted to the bottom-up approach of the Paris Agreement. The implications highlight the need for structural reforms within the GCF alongside strengthened domestic coordination and institutional capacity. The study concludes that the gap between commitments and finance access represents a systemic barrier requiring comprehensive policy responses.